Clinical and etiopathological profile of pancytopenia in children (1-18 years): A study from tertiary care center of Bundelkhand region, central India - Kumar, Vipin; Kankane, Aradhana; Pandey, Nupur (Indian Journal of Child Health, 2024)
Background: Pancytopenia is defined by a decrease in all three blood components, that is, leukopenia, thrombocytopenia, and anemia below the normal range. This study is an attempt to fill the lacunae regarding the information about pancytopenia in pediatric patients in the Bundelkhand region. The study aimed to study the clinical and etiopathological profile of pancytopenia in children (1–18 years) in the tertiary care center of the Bundelkhand region in central India. Materials and Methods: The present study was a hospital-based cross-sectional observational study conducted to learn about the clinical features, demographic and etiopathological profile of pancytopenia in children. The study was performed with 65 patients aged 1–18 years from September 2021 to August 2022 admitted to the Department of Paediatrics, Maharani Laxmi Bai Medical College and Hospital, Jhansi, and fulfilling inclusion criteria. IBM’s Statistical Package for the Social Sciences version 23 was used for the statistical study. Results: Out of 65 patients, a maximum number of cases were in the age group of 1–6 years (55%). Our study revealed male predominance over females with male-to-female ratio of 2.09:1, mostly belonging to rural areas. The most common presenting complaint was easy fatigue in (90%) of patients followed by fever (54%). The most common physical finding was pallor (100%), followed by splenomegaly and pedal edema (38%) and (18%), respectively. Bone marrow cellularity shows hypocellular marrow (62%), hypercellular (31%), and normocellular (7%). Peripheral smears of most of the patients showed normocytic normochromic (34%), followed by macrocytic hypochromic (30%). Regarding etiology megaloblastic anemia (30%) was reported as the most common cause of pancytopenia followed by malignancies (30%) including myelodysplastic syndrome (9%), multiple myeloma (3%), acute lymphocytic leukemia (9%), and acute myeloid leukemia (9%) followed by aplastic anemia (14%) and sepsis (8%). The study also shows other rare causes of pancytopenia such as disseminated tuberculosis (6%), malaria (9%), and dengue (3%). Conclusion: In the present study, the most common etiologies of pancytopenia come out as nutritional causes, that is, megaloblastic anemia followed by malignancies then aplastic anemia.